RADIATION FROM VICINITY OF SUPERMASSIVE OBJECT WITHOUT EVENTS HORIZON - Bannikova, E. Yu. (Одеські астрономічні публікації, 2017)
Spectra of the radiation arising at interaction of the spherically symmetric accreting flow with the matter of the atmosphere of the supermassive compact object without events horizon are found.